Effect of Substitution Sago Flour with Tempeh Flour and Emulsifier Types on Characteristic of Bangkit Cookies - Anugrahati, Nuri Arum; Wijaya, Luis F (AGRITEKNO: Jurnal Teknologi Pertanian, 2023)
Bangkit cookie is a traditional Indonesian cookie that is particularly popular among the Malay people on Sumatra Island, particularly in Riau Province. Bangkit cookies are composed entirely of sago flour, which contains a high carbohydrate but low protein content. Tempeh flour's high protein content is expected to enhance the protein content of the cookies. In addition, the usage of emulsifier will also be expected to improve the texture of the bangkit cookies. This study aimed to determine the best type of tempeh flour for various kinds of beans, i.e., soybeans, green beans, and red beans, based on their highest protein content and to identify the best ratio of tempeh flour to sago flour and the type of emulsifier in the bangkit cookies formula based on their texture and sensory acceptance. This research was divided into two stages. The first research stage used a Completely Randomized Design with 1 factor (soybeans, green beans, and red beans). The second stage of research used a Completely Randomized Design 2 factors (ratio of soybean tempeh flour:sago flour 0:100, 80:20, 60:40, 40:60) and types of emulsifier (egg yolks, soy lecithin, monoglyceride). Research result shows that 80:20, 60:40, and 40:60 ratios of sago flour to soybean tempeh flour with egg yolk emulsifier, soy lecithin, and monoglyceride, increased the protein content by an average of 7.15-21.53% and increased the hardness value of bangkit cookies. The best bangkit cookies are made from the ratio of sago flour and soybean tempeh flour 80:20 with egg yolk emulsifier and meet the SNI of cookies, which have 4.14% of moisture content, 8.95% of protein content, 622.99 hardness, and 3.7 of taste scored which is closest to the control.